Determination of Leisure Time Orientations in University Students, The Relationship Between Leisure Time Boredom Perceptions and Social Network Sites Usage Purposes - Nazlı Deniz Öz; Metin Özlü; Erdal Taşgın (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to determine the leisure time preferences of the university students and to examine the relationship between leisure time perception and usage of social network sitesThe research was conducted in accordance with the relational screening model. The study group consists of 230 female (65.7%), 120 male (34.3%), total 350 students studying at Konya Selçuk University. As a means of data collection in the study that personal information form, activity preference form and "Social Network Sites Usage Scale" developed by Karal and Kokoç (2010) and "Leisure Time Boredom Perception Scale" (LTBPS) developed by Iso-Ahola and Weissinger and adapted to Turkish by Kara et al. (2014) was used. SPSS 16.0 statistical package program was used to evaluate the data and to find the calculated values. The data are summarized by giving percent, mean and standard deviations. Independent group t test was used for binary cluster comparisons and One Way Variance Analysis (ANOVA) was used for multiple cluster comparisons due to the data showed normal distribution. Significance level in the study was taken as (p lt;0.05).